Innovative methods for solving the problem of female infertility associated with endocrine disorders - Sh. A. Anvarova; F. I. Shukurov; Sh. A. Tulametova (IRBIS LLC, 2020)
Aim: to analyze the publications assessing innovative methods of diagnostics and treatment used to solve the problem of female infertility associated with endocrine disorders.Materials and Methods. There was conducted a search for publications in electronic databases PubMed, Google Scholar, and eLibrary, which were selected in accordance with the PRISMA guidelines. All relevant articles published up to January 2024 were included in thereview. As a result, 374 publications retrieved from PubMed, 147 - from eLibrary, and 33- from Google Scholar were extracted. Duplicates and non-full-text versions of articles were excluded. After the selection procedure, 72 publications were included in the review.Results. During the data analysis, we identified key aspects providing deeper understanding of endocrine disorders affecting female infertility. In particular, new correlations were demonstrated between the level of select hormones and treatment success, as well as pathogenetic mechanisms were also identified influencing the conception and pregnancy process. These results will allow to develop more accurate diagnostic criteria and effective treatment methods able to increase women's chances of successful conception and pregnancy.Conclusion. The data analysis identified the hallmark aspects for diagnostics and treatment of female endocrine infertility, with new diagnostic criteria and effective treatment methods identified able to markedly improve outcomes. The crucial potential of the innovative approaches and methods considered contributes to improving reproductive health and increasing the chances of successful conception. We strongly encourage the introduction of such advanced technologies into clinical practice to optimize reproductive success.